2014
DOI: 10.1038/ncomms6515
|View full text |Cite
|
Sign up to set email alerts
|

Mybpc3 gene therapy for neonatal cardiomyopathy enables long-term disease prevention in mice

Abstract: Homozygous or compound heterozygous frameshift mutations in MYBPC3 encoding cardiac myosin-binding protein C (cMyBP-C) cause neonatal hypertrophic cardiomyopathy (HCM), which rapidly evolves into systolic heart failure and death within the first year of life. Here we show successful long-term Mybpc3 gene therapy in homozygous Mybpc3-targeted knock-in (KI) mice, which genetically mimic these human neonatal cardiomyopathies. A single systemic administration of adeno-associated virus (AAV9)-Mybpc3 in 1-day-old KI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 45 publications
10
93
1
4
Order By: Relevance
“…Murine models with altered sarcomere function have highlighted the importance of the early postnatal period in the pathogenesis of sarcomeric cardiomyopathy (8)(9)(10)(11)17). However, it has remained unclear why this developmental period is important in the pathogenesis of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine models with altered sarcomere function have highlighted the importance of the early postnatal period in the pathogenesis of sarcomeric cardiomyopathy (8)(9)(10)(11)17). However, it has remained unclear why this developmental period is important in the pathogenesis of disease.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent finding across multiple animal models of sarcomeric cardiomyopathy is that the early postnatal time period is important for both cardiomyopathy development and prevention of disease. Prevention of structural and functional defects associated with cardiomyopathy development has been demonstrated in murine models by viral reintroduction of wild-type protein and modulation of mutant RNA splicing or expression (8)(9)(10)(11). However, it remains unclear why this developmental time period is important in the pathogenesis of sarcomeric cardiomyopathies.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, for the studies described here, we assume that the phenotype of the Mybpc t/t mice is due to lack of MYBPC protein, rather than to small amounts of truncated protein. Recently, two groups have demonstrated that delivery of MYBPC to Mybpc3-null hearts restores cardiac function and morphology (19,20). Here, we have begun to dissect the mechanism by which homozygous Mybpc t/t hearts develop DCM.…”
Section: Significancementioning
confidence: 99%
“…In this regard, another obvious target is myosin binding protein C, which is the most commonly mutated protein in hypertrophic cardiomyopathy. Because most mutations cause disease through haploinsufficiency, gene therapy would be expected to be most effective in such conditions [107][108][109] . In skeletal and cardiac muscle, the balance between contraction and relaxation is readily shifted by physiological mechanisms…”
Section: Future Directionsmentioning
confidence: 99%